Teacher Strategies in Increasing Student Learning Interest with the Use of Science Lesson Image Media - Pasrellia, Reza; Disniarti (Lembaga KITA, 2024)
This study aims to identify teachers' strategies in increasing students' interest in learning through the use of image media in science learning at SD Tahfidz Abbil, Kota Pagar Alam. The research method used is qualitative descriptive with data collection techniques in the form of interviews, observations, questionnaires, and documentation. The results of the study show that teachers use various strategies such as the integration of image media in the lesson plan, the use of various types of images, interactive and participatory approaches, and creative projects. However, some of the challenges faced include limited access to high-quality media, longer preparation times, and inadequate technological skills. The effectiveness of the use of image media can be seen from the average increase in students' interest in learning by 25% and active participation during learning. Image media has also been shown to help students in understanding complex scientific concepts. The implications of this study show the need for continuous training for teachers in the use of technology and image media as well as increased access to better educational resources. Thus, the use of image media can be an effective strategy in increasing students' interest and understanding of science subjects.